Christ and the sense of time in the Andean and Amazonian traditions - Swanson, Tod (1989)
While it is true that there is not only one indigenous vision of Christ, this essay argues that it is possible to discern features of a characteristically indigenous Christology in the midst of the existing plurality. Based on Christological references taken from interviews, prayers and myths collected by anthropologists in the Andean and Amazonian areas, I have developed an interpretive model. This model can serve as a background for the study of emerging varieties of indigenous Christianity.